The impact of navigators on the satisfaction of patients with cancer: A Systematic Review - Herminah Winnie Firmus; Allenidekania Allenidekania; Tuti Nuraini; Yossie Susanti Eka Putri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Cancer is a disease or part of cells in the body that grows abnormally in parts of the human body and can spread to other parts of the body. Cancer can occur in children and adults. Patient navigators serve as intermediaries between individuals and the healthcare team, assisting patients in addressing and overcoming obstacles that may hinder access to medical services. They offer personalized support throughout the continuum of care, guiding patients through the various stages of their treatment journey. Purpose: To determine the effect of navigators on cancer patient satisfaction. Method: A systematic review approach in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The author used several research article databases, namely PubMed, ProQuest, Science Direct and Sage. 3 articles met the criteria and were analyzed and criticized using the JBI instrument. Results: Patient navigator is an effective strategy to improve diagnosis time, reduce anxiety, and increase patient satisfaction. Conclusion: The role of patient navigator in the context of cancer care can increase patient satisfaction and self-efficacy.